AUTHORIZED ECONOMIC OPERATOR: DIRECTIONS FOR IMPROVING UKRAINIAN LEGISLATION - KOLOMIIETS, Hanna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article presents an in-depth and detailed analysis of the theoretical foundations and legal characteristics of the Authorized Economic Operator (AEO) institution, with particular focus on its development and operational regulation in Ukraine. The study emphasizes the strategic importance of the AEO system as a tool for facilitating secure and efficient international trade, especially in the context of Ukraine’s aspiration to align with European Union (EU) standards and practices, as well as international norms on global supply chain security. The research highlights the fundamental role of AEOs in building mutual trust between businesses and customs authorities, promoting trade facilitation, and enhancing customs risk management. Special attention is given to the shortcomings and inconsistencies within the current Ukrainian regulatory framework that hinder the successful implementation of the AEO concept. These include the lack of a clear and enforceable distinction between AEO-C (customs simplifications) and AEO-S (security and safety), the absence of uniform and transparent criteria for evaluating financial reliability and compliance history of applicants, inadequate mechanisms for internal control and compliance monitoring, as well as weak interagency cooperation and an underdeveloped system for international mutual recognition of AEO status. The article further conducts a comparative legal analysis of European best practices, identifying successful regulatory approaches that may be adapted to Ukrainian realities. Based on this analysis, the authors propose a range of legislative and institutional reforms, such as the introduction of phased certification processes, development of standardized methodological guidelines, implementation of digital platforms for application processing and monitoring, and the establishment of a transparent and accountable audit system. Furthermore, the study advocates for enhanced state support in the form of informational, legal, and methodological assistance to businesses pursuing AEO status, especially small and medium-sized enterprises (SMEs). The proposed recommendations aim not only to address and eliminate existing legal and institutional barriers but also to promote broader engagement of economic operators, foster trust and cooperation between public and private sectors, and strengthen Ukraine’s integration into the EU customs framework. Ultimately, the implementation of these improvements is expected to boost the overall efficiency and transparency of Ukraine’s customs administration and contribute to the country’s economic resilience and competitiveness on the global market.